The Methodists and revolutionary America, 1760-1800 : the shaping of an evangelical culture - Andrews, Dee (Princeton University Press, 2000)
The Methodists and Revolutionary America is the first in-depth narrative of the origins of American Methodism, one of the most significant popular movements in American history. Placing Methodism's rise in the ideological context of the American Revolution and the complex social setting of the greater Middle Atlantic where it was first introduced, Dee Andrews argues that this new religion provided an alternative to the exclusionary politics of Revolutionary America. With its call to missionary preaching, its enthusiastic revivals, and its prolific religious societies, Methodism competed with.